The impact of financial cybercrimes on total quality standards according to Jordanian Islamic banks workers - Tarbeh, Ala’a Hashem (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the impact of financial cybercrimes on total quality standards according to employees of Islamic banks in Jordan. Adopting the descriptive analysis method, and design a questionnaire was applied to a random sample of (293) employee, and the following results were reached:1- According to Islamic banks employees, there is a negative impact of financial cybercrimes above mentioned.2- There is a negative impact of infrastructure's targeting crime with software on the total quality standards.3- There is a negative impact of the of payment's fraud crime represented by source misuse, and others misuse.4- The Percentage of the impact of all cybercrime on the total quality standards in the banking sector to those working in Islamic banks in Jordan is medium.And the study also concluded with several recommendations including work in to set up a banking system aimed at achieving information security in the banking sector to protect it from the risks of these crimes.
Keywords: electronic financial crimes; comprehensive quality; comprehensive quality standards; Islamic banks in Jordan